Battery operated fan and chronic breathlessness: does it help?. Issue Volume 9: Issue (2019)Supplement 4 (8th May 2019) - Barnes-Harris, Matilda; Allgar, Victoria; Booth, Sara; Currow, David; Hart, Simon; Phillips, Jane; Swan, Flavia; Johnson, Miriam J
Abstract : Objectives: To examine whether use of a hand-held fan ('fan') improves breathlessness and increases physical activity. Methods: A secondary exploratory analysis using pooled data from the fan arms of two feasibility randomised controlled trials in people with chronic breathlessness: (1) fan and activity advice vs activity advice, (2) activity advice alone or with the addition or the 'calming hand', or the fan, or both. Descriptive statistics and regression analysis to explore patient characteristics associated with benefit (eg age, sex, diagnosis, general self-efficacy). Results: Forty-one participants were allocated the fan (73 years (IQR 65–76, range 46–88), 59% male, 20 (49%) chronic obstructive pulmonary disease (COPD), three (7%) heart failure, three (7%) cancer). Thirty-five (85%) reported that the fan helped breathing, and 22 (54%) reported increased physical activity. Breathlessness benefit was more likely in older people, those with COPD and those with a carer. However, due to the small sample size none of these findings were statistically significant. Those with COPD were more likely to use the fan than people with other diagnoses (OR 5.94 (95% CI 0.63 to 56.21, p=0.120)). Conclusions: These exploratory data support that the fan helps chronic breathlessness in most people and adds new data to indicate that the fan is perceived to increase people's physical activity. There is also a signal of possible particular benefits in people with COPD which is worthy of further study.